A comprehensive adaptive system for e-learning of foreign languages. (30th December 2017) - Bradac, Vladimir; Walek, Bogdan
Highlights: We propose a new approach to adaptive e-learning systems. This approach uses detection of sensory preferences, didactic test and expert system. A complex model for adaptive e-learning system is described. The proposed approach is implemented and verified on real groups of students. Abstract: The article presents a proposal, design and implementation of a new approach to adaptive e-learning systems. First, a proposal of a model is presented. This model aims at introducing adaptivity to current e-learning systems, which are rigid and limited in offering a truly personalised learning to individual students. Many of current e-learning systems enable personalised learning. However, in this paper, there is a new, innovative approach proposed for an adaptive personalised e-learning system. The primary area of our research is English as a second language (ESL). Adaptivity in our view is considered as an ability of the system to adapt to student's knowledge and characteristics. This pedagogical perspective requires introduction of such processes that enable to work the pedagogical aspects of teaching/learning. The required processes are of informatics nature. The proposed model was subsequently designed into a real application. Finally, the application was implemented and verified on a real data set. The results are also provided.